2022
DOI: 10.33369/jk.v6i1.20231
|View full text |Cite
|
Sign up to set email alerts
|

Profile Of Physical Fitness Basketball Student Extracurricular

Abstract: The purpose of this study was to determine the level of physical fitness of students participating in basketball extracurricular training. This research is descriptive quantitative with survey methods. TKJI test and measurement (Indonesian physical fitness test) to determine the level of physical fitness in students. The research sample consisted of 20 male students in extracurricular basketball at Madrasah Tsanawiyah Negeri 1 Pontianak. The data obtained in the field are the results of TKJI aged 13-15 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results showed that its energy expenditure was 4319.98±525.95 kcal when climbing in 11 hours. 12 The study of body weight and body composition showed that the subjects lost 2.6 kilograms of body weight and about 1% of their fat. When it comes to climbing, thin people do not change much.…”
Section: Body Composition and Muscle Coordinationmentioning
confidence: 99%
“…The results showed that its energy expenditure was 4319.98±525.95 kcal when climbing in 11 hours. 12 The study of body weight and body composition showed that the subjects lost 2.6 kilograms of body weight and about 1% of their fat. When it comes to climbing, thin people do not change much.…”
Section: Body Composition and Muscle Coordinationmentioning
confidence: 99%
“…Swimming activity is an important resource so as not to drown [10], besides that it also requires good and prime physical condition. Thus, physical fitness is also maintained [11,12,13,14,15], which is related to physical health [16,17,18]. A study based on the results of clinical trials showed that swimmers found specific improvements in lung function [19].…”
Section: Introduction 1smentioning
confidence: 99%